The effects of Lactobacillus and/or Bifidobacterium in fermented foods on cognitive health: a systematic review - Harsa, Hayriye Sebnem; González Domenech, Carmen María; Prvulović, Milica; Agirbasli, Zeynep; Bagherzadehsurbagh, Erfan; Simeunović, Valentina; Naziri, Eleni; Adesemoye, Elizabeth; Yigit Cinar, Aycan; Mukherjee, Arghya; Laranjo, Marta; Vidović, Bojana; et al. (Frontiers in Nutrition, 2025)
BackgroundPsychobiotics are microorganisms that modulate brain function via the gut–brain axis and are increasingly studied for their cognitive benefits. Lactobacillus and Bifidobacterium species, widely present in fermented foods, are considered safe and may influence cognition by modulating neuroinflammation, neurotransmitters, and gut barrier integrity. This systematic review examined the effects of foods fermented with these species on cognitive performance in healthy adults and individuals with mild cognitive impairment.MethodsWe conducted the systematic review following EFSA guidelines, Cochrane methodology, and a PROSPERO protocol, using CADIMA for study selection and data extraction. PubMed, Scopus, and Cochrane Library were searched (1 January 1970–31 August 2023) for human intervention and observational studies assessing cognitive outcomes after ingestion of foods fermented with Lactobacillus or Bifidobacterium. Eligible populations included healthy adults and individuals with mild cognitive impairment; studies involving disease were excluded. Screening, data extraction, and bias assessment followed Muka et al.’s 24-step guide using ROBINS and Cochrane/CADIMA frameworks. Evidence was synthesized narratively, while a non-systematic component examined food characteristics, potential mechanisms, and factors affecting bioavailability of bioactive constituents.ResultsWe included 21 studies (8 interventional, 13 observational). The majority of studies reported benefits, particularly in episodic memory, executive functions, and global cognition, but evidence was limited by inadequate controls, small sample sizes, short interventions, inconsistent domain assessment, and incomplete food characterization. Observational studies had larger populations and longer follow-ups but were limited by exposure assessment and depth of cognitive testing.ConclusionConsumption of foods fermented with Lactobacillus and/or Bifidobacterium species may offer promising cognitive benefits. However, following EFSA’s guidance on the substantiation of health claims, the current evidence is “neither convincing nor sufficient” to establish a causal relationship. Well-designed studies with thorough product characterization are needed to substantiate effects and support potential health claims.Systematic review registrationThis study was registered at the Open Science Framework (10.17605/OSF.IO/Z6GRW).